Eksploitasi dan Konservasi Sumberdaya Hayati Laut dan Pesisir di Indonesia - Hengky K. Baransano; Jubhar C. Mangimbulude (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Based on the Central Bureau of Statistics (BPS), the total population in 2010 is predicted to reach 231 million people, or increase 29 million people compared with the 2000 population census data report, which recorded 202 million people. This condition demands the availability of food, clothing, and shelter. One of the solutions to manage human needs is by exploiting sea life and shoreline resources in Indonesia. Indonesia is an archipelago with its enormously potential sea life resources and shorelines. Over utilizing sea life resources can damage the sea and shoreline ecosystems. The efforts have been conducted to protect a balance in building and continuing sea life in water and sea life ecosystems through the conservation done by society, scientists, and the government. In this scientific review, the shoreline and sea life resources in Indonesia are revealed.Key words: exploitation, conservation, sea life resources, shoreline, sea.